Charting the academic output on cyanobacterial exopolysaccharides and their industrial applications - Maricel BOCANEALA; Giovani M. GORON; Elena RAKOSY-TICAN (Studia Universitatis Babeș-Bolyai. Biologia, 2025)
Cyanobacterial exopolysaccharides (EPS) are diverse biopolymers with significant ecological roles and growing industrial potential due to their biocompatibility, biodegradability, and functional versatility. This study presents a bibliometric and patent analysis of cyanobacterial EPS research between 2004 and 2023, exploring academic and industrial advancements. The bibliometric analysis of 1,022 articles identified pharmaceuticals and environmental applications as dominant research themes, while the food, agriculture, and energy sectors showed emerging interest. A manually curated subset of 79 articles focusing on industrial applications highlighted EPS’s potential in pollutant removal, drug development, and biofertilization. Patent analysis, with data from 618 entries, revealed a surge in filings post-2014, predominantly in the USA, reflecting growing industrial interest. While healthcare and environmental sectors lead in EPS applications, translational gaps between academic research and industrial adoption persist, particularly in underdeveloped domains. This study presents the multidisciplinary appeal of cyanobacterial EPS, striving to offer insights into future research directions and their potential for sustainable innovation across diverse sectors. Article history: Received 4 February 2025; Revised 17 March 2025; Accepted 17 March 2025; Available online 25 June 2025